Mapping chatbot types and features : case rescue services - Reijo, Aleksanteri (2022)
The subject of this thesis is the feature needs of a regionally localized chatbot offered by SKRS (South-Karelian Rescue Services) on their home page. The study used literature to find what types of chatbots exist. Interviews with SKRS staff were held to find what types of features and technologies are needed to best achieve the goals of the chatbot project. The goals specifically relate to how South-Karelian customers can best be served with the rescue services' human and information resources. Based on interviews and theory it was deemed that the best feature set to pursue included neural network-based NLP (Natural Language Processing) and a set of features that aid in better serving SKRS's customers the information they need. Tämän työn aiheena on Etelä-Karjalan Pelastuslaitoksen tarjoama chattibotti ja sen paikallistaminen. Tutkimus tutki kirjallisuutta selvittämään minkälaisia chattibotteja on olemassa. Etelä-Karjalan Pelastuslaitoksen työntekijöitä haastateltiin jotta voitaisiin selvittää minkälaisia ominaisuuksia ja teknologioita tarvittaisiin chattibottiprojektin tavoitteiden saavuttamiseksi. Tarkemmin sanottuna tavoitteet liittyvät siihen miten Etelä-Karjalalaisia asiakkaita pystyy parhaiten palvelemaan Pelastuslaitoksen työvoima- ja tietoresursseilla. Haastatteluihin ja teoriaan perustuen paras joukko toimintoja tavoitella sisältää neuroverkkoihin perustuvan luonnollisen kielen käsittelyyn perustuvan lauseiden luokittelun ja joukon ominaisuuksia joita käytetään pelastuslaitoksen asiakkaiden tarpeiden selvittämiseen ja kattamiseen.